Disruption of PCNA-lamins A/C interactions by prelamin A induces DNA replication fork stalling. (2nd September 2016) - Cobb, Andrew M.; Murray, Thomas V.; Warren, Derek T.; Liu, Yiwen; Shanahan, Catherine M.
ABSTRACT: The accumulation of prelamin A is linked to disruption of cellular homeostasis, tissue degeneration and aging. Its expression is implicated in compromised genome stability and increased levels of DNA damage, but to date there is no complete explanation for how prelamin A exerts its toxic effects. As the nuclear lamina is important for DNA replication we wanted to investigate the relationship between prelamin A expression and DNA replication fork stability. In this study we report that the expression of prelamin A in U2OS cells induced both mono-ubiquitination of proliferating cell nuclear antigen (PCNA) and subsequent induction of Pol η, two hallmarks of DNA replication fork stalling. Immunofluorescence microscopy revealed that cells expressing prelamin A presented with high levels of colocalisation between PCNA and γH2AX, indicating collapse of stalled DNA replication forks into DNA double-strand breaks. Subsequent protein-protein interaction assays showed prelamin A interacted with PCNA and that its presence mitigated interactions between PCNA and the mature nuclear lamina. Thus, we propose that the cytotoxicity of prelamin A arises in part, from it actively competing against mature lamin A to bind PCNA and that this destabilises DNA replication to induce fork stalling which in turn contributes to genomic instability.